Math, asked by sahil620, 1 year ago

1 + cos theta + sin theta upon 1 + cos theta minus sin theta equal to 1 + sin theta upon cos theta

Answers

Answered by isyllus
349

Answer:

Hence Proved

Step-by-step explanation:

To prove:

\dfrac{1+\cos\theta+\sin\theta}{1+\cos\theta-\sin\theta}=\dfrac{1+\sin\theta}{\cos\theta}

Proof: We start from left side,

\Rightarrow \dfrac{1+\cos\theta+\sin\theta}{1+\cos\theta-\sin\theta}

Divide by \cos\theta at top and denominator and we get

\Rightarrow \dfrac{\sec\theta+1+\tan\theta}{\sec\theta+1-\tan\theta}

\Rightarrow \dfrac{\sec\theta+\tan\theta+\sec^2\theta-\tan^2\theta}{\sec\theta+1-\tan\theta}

\text{Using formula, }a^2-b^2=(a+b)(a-b)

\Rightarrow \dfrac{(\sec\theta+\tan\theta)(\sec\theta+1-\tan\theta)}{\sec\theta+1-\tan\theta}

\Rightarrow \sec\theta+\tan\theta

\sec\theta=\dfrac{1}{\cos\theta}\text{ and }\tan\theta=\dfrac{\sin\theta}{\cos\theta}

\Rightarrow \dfrac{1}{\cos\theta}+\dfrac{\sin\theta}{\cos\theta}

\Rightarrow \dfrac{1+\sin\theta}{\cos\theta}=RHS=\dfrac{1+\sin\theta}{\cos\theta}

LHS=RHS

Hence Proved

Answered by amanmishrarewa23
41

Answer:

Hope it helps you.....

Attachments:
Similar questions